Categorization, Appraisal, and Reporting of Medication Errors Ascertained in Medical Ward of Tertiary Care Hospital - Vinodkumar Mugada, Reethu Chowdary Devineni, Reena Mounika Pendyala, Dilipkumar Vempati, Sarathchandra Kuchi (Journal of Applied Pharmaceutical Science, 2018)
The purpose of the present study was to categorize, assess and report medication errors. The descriptive cross-sectional study was conducted on 377 patients in the department of general medicine for six months. Medication error reporting form (MERF) is used as study instrument. The higher prevalence rate is seen in prescribing errors. Mostly seen prescribing errors were omission of doses, omission of frequency, abbreviated forms, labeling and set of instructions, brand a name and dosage form omission in our study. Medication errors were mostly seen in drugs belonging to the classes of antibiotics, antihypertensive drugs, antipyretics, and diuretics. The possible contributing factors for medication errors in our present study were illegible prescription, failure to adhere to work procedure, peak hour, and abbreviated form, labeling and set of instructions, and miscommunication. Look-alike/sound-alike is the responsible cause of the dispensing centered errors. Education and training to nursing staff, improvement in communication process helps to minimize the prescribing errors.
Keywords: Medication errors, prescribing errors, categorization, prescription.